Tolerability of endometriosis medical treatment: a comparison between combined hormonal contraceptives and progestins - Denise Joffily Pereira da Costa Pinheiro; Ana Maria Gomes Pereira; Marcelo Antonini; Isabella Maria Albuquerque Salgado; Alexandre Torchio Dias; Reginaldo Guedes Coelho Lopes (BMC, 2023)
Abstract Endometriosis is a chronic inflammatory disease that occurs in women of reproductive age. Much of the treatment involves hormone therapy that suppresses the proliferation of endometriosis lesions. Objective To compare discontinuation rates of pharmacological treatment with estrogen-progestins and progestins medications. The secondary objective is to evaluate the main side effects of these drugs in patients with endometriosis. Methods This retrospective study analyzed data from 330 patients who attended the Hospital of the State Public Servant of São Paulo from August 1999 to September 2020 and received pharmacological treatment for endometriosis. The data were obtained by review of the files of medical appointments with specialized staff. Results The median treatment time was 18 months, ranging from 1 to 168 months, and 177 patients interrupted the proposed treatment. The combined contraceptives with estrogens and progestins were significantly linked to treatment interruption, with a relative risk of 1,99 (p = 0,005). The most important side effects that resulted in treatment interruption were pain persistence (p = 0,043), weight gain (p = 0,017) and spotting (p < 0,001).